The effect of socioemotional wealth on the relationship between entrepreneurial orientation and family business performance - Remedios Hernández-Linares; Franz W. Kellermanns; María C. López Fernández; Soumodip Sarkar (BRQ Business Research Quarterly, 2020)
This study examines how five key entrepreneurial orientation (EO) dimensions-risk taking, innovativeness, proactiveness, competitive aggressiveness, and autonomy-affect family business performance, as well as the moderating effect of socioemotional wealth (SEW) on these relationships. The findings, based on a sample of 609 Spanish and Portuguese family firms, reveal that not all EO dimensions are equally important for performance, as only proactiveness, competitive aggressiveness, and autonomy were significant. However, we also find that the EO-performance relationship is affected by concern for SEW preservation, as our SEW measure moderates risk taking positively and innovativeness negatively.
Keywords: 650; Entrepreneurial orientation; firm performance; family firm; socioemotional wealth